2016
DOI: 10.1038/srep31973
|View full text |Cite|
|
Sign up to set email alerts
|

A ruthenium polypyridyl intercalator stalls DNA replication forks, radiosensitizes human cancer cells and is enhanced by Chk1 inhibition

Abstract: Ruthenium(II) polypyridyl complexes can intercalate DNA with high affinity and prevent cell proliferation; however, the direct impact of ruthenium-based intercalation on cellular DNA replication remains unknown. Here we show the multi-intercalator [Ru(dppz)2(PIP)]2+ (dppz = dipyridophenazine, PIP = 2-(phenyl)imidazo[4,5-f][1,10]phenanthroline) immediately stalls replication fork progression in HeLa human cervical cancer cells. In response to this replication blockade, the DNA damage response (DDR) cell signall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 60 publications
7
58
0
Order By: Relevance
“…Recent proofof-principle studies on organometallic NHC anticancer agents showed that this class of compounds is able to target several canonical and non-canonical DNA secondary structures. In detail, metal NHC complexes were shown to interact with duplex, mismatched and Gquadruplex DNA, while examples of other classes of metal-based anticancer agents exist that inhibit replication forks, 89 by interacting with DNA three-way junctions, 90 spectroscopy and isotope-specific mass spectrometry would allow to follow not only the compounds distribution in cells, but also the structural integrity of the compound, e.g. with regard to ligand exchange reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent proofof-principle studies on organometallic NHC anticancer agents showed that this class of compounds is able to target several canonical and non-canonical DNA secondary structures. In detail, metal NHC complexes were shown to interact with duplex, mismatched and Gquadruplex DNA, while examples of other classes of metal-based anticancer agents exist that inhibit replication forks, 89 by interacting with DNA three-way junctions, 90 spectroscopy and isotope-specific mass spectrometry would allow to follow not only the compounds distribution in cells, but also the structural integrity of the compound, e.g. with regard to ligand exchange reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the potential benefits and application of these complexes in combination therapy for cancer treatment warrants further investigation. 22 Recently, Koceva-Chyła et al evaluated the in vitro anticancer activity of dinuclear trithiolato-bridged arene ruthenium complex diruthenium-1 (DiRu-1) against a panel of human cancer cell lines including HepG2 (hepatocellular carcinoma), MCF-7 (estrogen-responsive breast adenocarcinoma), and MDA-MB-231 (triple-negative breast adenocarcinoma) cells. DiRu-1 was found to be extremely toxic to these cell lines, with half-maximal inhibitory concentration (IC 50 ) values in the low-nanomolar range.…”
Section: (Pip)]mentioning
confidence: 99%
“…11,10,53,54 Many researchers have suggested that effective therapy for cancer or efficient ways of treating a cancer patient essentially depends on the antimetastatic activity of the chemotherapeutic PS drugs. 3,10 from the MTT assay, it is evident that these two complexes have good potential for interrupting cancer cell proliferation in the presence of visible light.…”
Section: Wound Healing Assaymentioning
confidence: 99%
“…8,9 The possibility of achieving high solubility by choosing appropriate counter anions or through appropriate functionalization of the coordinated ligands has led to the design of new Ru(II)-polypyridyl complexes for use of anti-cancer and antimetastatic drugs. 10,11 These complexes are attractive choices for use as photodynamic therapeutic reagents and they also possesses visible light excitation, reasonably long-lived triplet excited states, and higher stability towards photobleaching. 7 Recent reports suggested that the conjugation of biologically relevant molecules to the Ru(II)-polypyridyl complexes can improve cellular internalization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation